Pharmacoeconomic effectiveness of using modern technologies in the follow-up care of patients with arterial hypertension - A. Yu. Efanov; I. V. Medvedeva; S. V. Shalaev; I. M. Petrov; E. Yu. Yusupova; S. Yu. Volkova; Yu. A. Petrova (Российский кардиологический журнал, 2019)
Aim. To conduct a pharmacoeconomic assessment of the use of modern technologies in the follow-up care of patients with arterial hypertension (AH) in the Tyumen region.Material and methods. Using a random sampling technique we selected and examined 1704 patients with AH in the Tyumen region. The average age of patients was 62±75 years, 31,5% were men. Patients are divided into active monitoring and control groups. Weekly sms and e-mail messages with prevention information were sent to patients of the active monitoring group. General practitioners receive a course of training seminars on the features of follow-up observation of patients with AH. After 12 months (±3,2), the patients had repeated examination. We conducted pharmacoeconomic analysis of the intervention.Results. The results of our study showed that the total cost of the disease with active follow-up of patients with AH decreases, which mainly occurs due to indirect expenses. Weekly sms and e-mail notification of patients in combination with educational seminars for general practitioners and cardiologists leads to a change in the structure of expenses for the treatment of patients with AH. We noticed reducing the cost of inpatient treatment, emergency calls, and a decrease in indirect expenses. On the other hand, there is a redistribution of funds spent on pharmacotherapy and cases of outpatient visits. Such redistribution, combined with a decrease in the total cost of the disease, leads to savings in the resources of the health care system and allows an additional 231 patients to be treated within 12 months.Conclusion. The proposed model of active follow-up is economically viable, both by reducing the total cost of the disease, and by redistributing funds towards using pharmacotherapy and outpatient visits, which is the most rational in the treatment of AH.